PENGOPTIMALAN DAN PENGEMBANGAN POTENSI UMKM DARI HASIL LAUT DI DESA EKAS BUANA, KECAMATAN JEROWARU KABUPATEN LOMBOK TIMUR - Dharmawan, Rizky; Saputri, Gina Mailinda; Andriana, Larasati; Larasati, Baiq Nita; Aini, Kurratin; Adi, Morista Kencana; Riadi, L. Samsul; Mariani, Alinda Ayu; Irfan, M. Syauqi; olehani, Winarti S (Universitas Mataram, 2024)
Indonesia has significant potential in the blue economy, particularly in the marine and fisheries sector. Desa Ekas Buana, located in Lombok Timur Regency, West Nusa Tenggara, is one of the villages with such potential; however, the local community faces various challenges in optimally utilizing marine resources. To address these issues, a Community Service Program (KKN) conducted by UNRAM students in Desa Ekas Buana aims to enhance community skills through training in the production of fish floss (abon ikan) and business licensing socialization. The fish floss production training focuses on the village women to increase the added value of the abundant marine products. Meanwhile, the business licensing socialization aims to help MSME entrepreneurs understand the importance of business legality, open access to various facilities, and prepare them for wider market opportunities. This program received positive responses from both the community and the village government, demonstrating its success in empowering the community through marine product processing and business legality.